Deteksi Penyakit Diare Pada Anjing Menggunakan Metode Case Based Reasoning - Puteri Diyana; Yani Maulita; Magdalena Simanjuntak (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
In Indonesia, people keep a lot of animals, such as dogs. Dogs are one of the favorite animals commonly kept by humans. Dogs are usually favorite animals that can be used as companions, guarding the house, hunting and so on. Alvi Deiectiones (Diarrhea) disease is caused by eating food errors (such as eating leftover or stale food), changing types of food without a transition period, viral, bacterial, or parasitic infections.One of the problems often encountered at the Binjai Petshop clinic is diarrheal disease in dogs. The lack of knowledge in people who keep dogs about diarrhea disease and the limited existence of veterinary clinics, time and money make many cases of improper treatment that worsen the dog's condition. To help overcome this problem is to create an Expert System that can diagnose diseases based on the symptoms that occur to detect the disease experienced. Expert System can be interpreted as a collection of facts that have been collected to show the symptoms of a disease and can provide an explanation based on consultation with the expert.